Creativity and its paradoxes: How the Indonesia movie industry can survive - Elvy Maria Manurung; Daniel Daud Kameo (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2021)
Creativity is the driving force of the global economy. Competitors will arguably outcompete companies that cannot accelerate creativity in terms of technology and innovation. Highly reliant on creativity, the movie industry exhibits tensions and dilemmatic situations from time to time. On the one hand, creativity is needed to produce high-quality cultural products. On the other hand, commercial success and market acceptance are crucial for survivability. This research explores the Indonesian movie industry in terms of creativity and commerciality and its relationship with the creativity paradox that is relatively understudied before. The research was conducted in 2015-2017 using the grounded method. We conducted several interviews with moviemakers and audiences and organized focused group discussions with experts (film-culture critics). The results show that filmmakers need to recognize this paradoxical situation and manage their creativity better. Besides cinematography and story-telling skills, a better understanding of consumer behavior, marketing strategies, innovation, and financing strategies are important factors in managing creativity in the movie industry.